THE EFFECT OF AUDIT TENURE, TAX MINIMIZATION, AND DEBT COVENANT ON TRANSFER PRICING - Nabilah Aulia Azmi; Mohamad Zulman Hakim; Putri Rahayu; Reni Nasiatul Hamidah (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study examines the influence of audit tenure, tax minimization, and debt covenants on transfer pricing practices in industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. A quantitative research approach was employed using secondary data from companies’ annual reports and financial statements. Through purposive sampling, 18 companies were selected, yielding 72 firm-year observations. Data were analyzed using panel data regression with EViews 12. Model selection tests, including the Chow test, Hausman test, and Lagrange Multiplier test, indicated that the Random Effects Model was the most appropriate estimation method. The findings show that transfer pricing is positively and significantly influenced by audit tenure, suggesting that longer auditor–client relationships enhance auditors’ ability to monitor and identify related-party transactions. Conversely, transfer pricing is negatively affected by tax minimization, proxied by the effective tax rate, and debt covenants, measured by the debt-to-equity ratio. Collectively, audit tenure, tax minimization, and debt covenants simultaneously influence transfer pricing, although the adjusted R-squared value of 12.16% indicates that transfer pricing practices are largely explained by factors outside the model. These findings offer insights for regulators and companies regarding the importance of auditor oversight in promoting transparency and compliance in related-party transactions.